Including the invisible: deep depth-integrated chlorophyll estimates from remote sensing may assist in identifying biologically important areas in oligotrophic coastal margins - R. P. Schoeman; C. Erbe; R. D. McCauley (Biogeosciences)
Surface chlorophyll from satellite remote sensing is a common predictor variable in marine animal habitat studies but fails to capture deep chlorophyll maxima (DCMs) that are unambiguous in persistently stratified water columns. DCMs are also present within the meso-oligotrophic marine environment of Western Australia and have been hypothesised to be an important feature for the growth and maintenance of regional krill populations on which locally endangered pygmy blue whales feed. This study used ∼8500 vertical ocean glider profiles collected between 2008 and 2021 to better understand the broad-scale temporal presence of DCMs and their characteristics in Western Australian waters. Our results show that DCMs are predominantly present from September to April, with a high proportion of biomass maxima within the euphotic zone in September and March. In summer, DCMs deepen and settle below the euphotic zone. The latter results in a balanced presence of biomass and photo-acclimation maxima, placing Western Australian waters in a unique biogeographical biome. In addition, since DCMs in summer contribute over 50 % to water-column-integrated chlorophyll below the euphotic zone, our results are in support of hypotheses regarding the importance of the DCM for local krill and highlight the need to develop methods to include water-column-integrated chlorophyll estimates in habitat models. Linear regression analyses show that this could be achieved through the extension of previously known relationships between surface and water-column-integrated chlorophyll over the euphotic zone to twice the euphotic zone depth (i.e. deep depth-integrated chlorophyll). While using water-column-integrated chlorophyll estimates from satellite remote sensing has its challenges, it is currently the only means to include DCMs in habitat models fitted to large temporal- or spatial-scale animal presence data.